Effects of wildfire ashes from different plant coverages in aquatic life stages of amphibians - Santos, Diogo Gabriel Coutinho dos (2023)
Climate change has led to a global increase of earth surface temperatures. This phenomenon triggered the increase of frequency and intensity of extreme events such as wildfires. Mediterranean countries are severely affected by these disturbances because of their especially dry summers. Wildfire situation in Portugal is especially critical, because besides the hot and dry summers its native forests have been replaced with monospecific plantations that facilitate wildfires. Wildfires, along with the ashes formed, may cause environmental impacts. Formation of the ashes is a process that converts fuels (organic matter) into a matrix composed of organic and inorganic compounds. Plant coverage can alter the ashes’ chemical and physical properties, especially in ashes with a high organic fraction. During the first rain events post-wildfires, these ashes, with the adsorbed chemicals, are transported into nearby waterbodies, where they can induce adverse effects to aquatic biota. Early-life stages of amphibian (embryos and tadpoles) may be particularly susceptible to these chemicals and ashes. According to the above, this study intended to assess how ashes originated from wildfires of forests with different plant coverages (Eucalyptus globulus and Pinus pinaster) affect embryos or tadpoles of two species of amphibians – Xenopus laevis and Pelophylax perezi. In order to do so, embryos of X. laevis and tadpoles of the two species of amphibians were exposed for 96 h and 14 days, respectively, to serial concentrations (26.9% - 100%) of aqueous extracts of ashes (AEA, with 10 g/L of ashes) containing Eucalypt (ELS) and Pine (PLS) ashes. At the end of the assays, the following endpoints were measured: mortality, developmental stage, body length (total, snout-to-vent-SV, tail) and weight. Effects at sub-individual level were also monitored for oxidative stress (catalase-CAT, glutathione-S-transferase-GST, total glutathione-TG, and lipidic peroxidation-LPO), neurotoxicity (acetylcholinesterase-aChE), and energy metabolism (oxygen consumption through the electron transfer system-ETS, and carbohydrate, lipid and protein contents). Chemical characterization of ashes and AEA was also performed. The AEA of ELS showed higher concentrations of As, Cd, Co, Cr, Pb and V, while PLS showed higher concentrations of Cu, Mn, Ni and Zn. Though a mortality above 20% occurred in embryos of X. laevis exposed to AEA, it was not significantly different from the control. Effects at sublethal level were only observed for embryos exposed to PLS; which showed lower carbohydrates content and higher oxygen consumption. Exposure of tadpoles of X. laevis to ELS and PLS AEA caused some mortality, that was not significantly different from the control, and a delay in developmental stages. All tested concentrations of the two AEA significantly decrease the body lengths and body weight of X. laevis tadpoles. At the sub-individual level, a decrease in the activity of the enzymes CAT and GST and in carbohydrates and lipid contents were observed in these organisms. An increase in oxygen consumption was only registered for tadpoles exposed to PLS. As for tadpoles of P. perezi, exposure to ELS induced no significant effects in the organisms. Though exposure to PLS caused a reduction in body lengths, weight, GST activity and an increase in oxygen consumption. Overall, PLS AEA induced more effects in the two species, suggesting an influence of vegetation cover in the toxicity of ashes. Tadpoles of X. laevis showed a higher sensitivity to the AEA than the respective embryos and than of P. perezi, suggesting to be an adequate model organism for the risk assessment of ashes derived from wildfire to amphibians. Further, the obtained results showed that short-term exposure to ash-load runoffs from eucalypt or pine forests may compromise amphibian’s populations.